Employee Performance and Mental Well-Being: The Mitigating Effects of Transformational Leadership during Crisis - Kristina Czura; Florian Englmaier; Hoa Ho; Lisa Spantig (Center for Economic Studies and ifo Institute (CESifo), 2023)
The positive role of transformational leadership on productivity and mental well-being has long been established. Transformational leadership behavior may be particularly suited to navigate times of crisis which are characterized by high levels of complexity and uncertainty. We exploit quasi-random assignment of employees to managers and study the role of frontline managers' leadership styles on employees' performance, work style, and mental well-being in times of crisis. Using longitudinal administrative data and panel survey data from before and during the Covid-19 pandemic, we find that frontline managers who were perceived as having a more transformational leadership style before the onset of the pandemic, led employees to better performance and mental well-being during the pandemic.
Keywords: M54; M12; J53; 330; leadership; frontline managers; labor-management relations; organizational behavior; crisis